A flame retardant ABS composite material and preparation method thereof

By adding a flame retardant prepared by specific chemically modified antimony trisulfide to ABS, the problem of insufficient flame retardant performance of ABS materials is solved, and the excellent flame retardant performance and good physical properties of ABS composites are achieved, which expands its application range.

CN119775708APending Publication Date: 2025-04-08CHUZHOU GEMEITE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411953987.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing ABS materials have insufficient flame retardant performance in some specific application areas, limiting their application scope.

Method used

Diantimon trisulfide is prepared by adding specific flame retardants to ABS, including reactions of antimony nitrate, thiourea, ethanol and deionized water, and a novel flame retardant with excellent flame retardant properties is formed by modification of 3-mercapto-2-methylpentanol and 2-ethoxy-1-naphthoyl chloride.

Benefits of technology

The flame retardant properties of ABS composites are significantly improved and expand their application potential in specific fields without affecting their physical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215463780000011
    Figure BDA0005215463780000011
  • Figure BDA0005215463780000021
    Figure BDA0005215463780000021
  • Figure BDA0005215463780000091
    Figure BDA0005215463780000091
Patent Text Reader

Abstract

The invention discloses a flame retardant ABS composite material and a preparation method thereof, wherein the flame retardant ABS composite material is made of the following components in parts by weight: 90 parts to 110 parts of ABS, 18 parts to 24 parts of flame retardant, 0.1 parts to 0.3 parts of compatibilizer, and 0.1 parts to 0.5 parts of antioxidant; the preparation method of the flame retardant is as follows: firstly, antimony trisulfide is synthesized, and then it is modified with 3-mercapto-2-methylpentanol to obtain antimony trisulfide modified with 3-mercapto-2-methylpentanol, and finally it is modified with 2-ethoxy-1-naphthoyl chloride to obtain the flame retardant of the present invention. The flame retardant in the present invention introduces more benzene ring structures through modification, and in the combustion process, the benzene ring structure can form a dense carbon layer, which can isolate the transfer of heat and oxygen, thereby preventing or slowing down the combustion process, and can well improve the flame retardant properties of the ABS composite material, which has great promotion value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a flame-retardant ABS composite material and a preparation method thereof. Background Art

[0002] Acrylonitrile-styrene-butadiene copolymer (ABS) is a widely used polymer polyester resin. ABS has the advantages of good fatigue resistance, good heat resistance, excellent dimensional stability, etc. However, in some specific application fields, ABS has higher requirements for flame retardancy. Ordinary ABS materials can no longer meet this requirement, which limits the application of ABS composite materials in some specific fields.

[0003] In view of this situation, the present invention innovatively produces a new type of ABS composite material, which has excellent flame retardant properties. This material has not been reported so far, which has very important practical significance for expanding the application of ABS composite materials. Summary of the invention

[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a flame retardant ABS composite material and a preparation method thereof. The present invention adds a specific flame retardant to ABS to make ABS have excellent flame retardant properties.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A flame retardant ABS composite material, which is made of the following components in parts by weight:

[0007]

[0008] The preparation method of the flame retardant is as follows:

[0009] S1. Place antimony nitrate, thiourea, ethanol and deionized water into a reaction vessel, and react in a water bath at 70-90° C. for 10-16 hours to obtain a first mixed solution.

[0010] S2. Filter the first mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 60-90° C. for 8-14 hours to obtain antimony trisulfide.

[0011] S3. Put antimony trisulfide, 3-mercapto-2-methylpentanol, ethanol and deionized water into a reaction vessel, and react in a water bath at 70-80° C. for 12-16 hours to obtain a second mixed solution.

[0012] S4. Filter the second mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 70-90° C. for 8-12 hours to obtain antimony trisulfide modified with 3-mercapto-2-methylpentanol.

[0013] S5. Put antimony trisulfide modified with 3-mercapto-2-methylpentanol, 2-ethoxy-1-naphthoyl chloride, N,N-dimethylformamide, ethanol and deionized water into a reaction vessel, and react in a water bath at 70-80° C. for 12-16 hours to obtain a third mixed solution.

[0014] S6. Filter the third mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 60-90° C. for 6-12 hours to obtain antimony trisulfide modified with 2-ethoxy-1-naphthoyl chloride, which is a flame retardant.

[0015] The chemical reaction equation involved in the above reaction process is as follows:

[0016] 3CH4N2S+2Sb(NO3)3→Sb2S3+3CH4N2(NO3)2

[0017] CH4N2(NO3)2+H2O→2NH3+CO2+HNO3

[0018]

[0019] Preferably, the mass ratio of antimony nitrate, thiourea, ethanol and deionized water in step S1 is (30-40): (36-40): (60-80): (100-160).

[0020] Preferably, the mass ratio of antimony trisulfide, 3-mercapto-2-methylpentanol, ethanol and deionized water in step S3 is (30-40):(8-10):(50-60):(90-110).

[0021] Preferably, the weight ratio of 3-mercapto-2-methylpentanol modified antimony trisulfide, 2-ethoxy-1-naphthoyl chloride, N,N-dimethylformamide, ethanol and deionized water in step S5 is (28-32): (10-14): (40-48): (50-60): (70-90).

[0022] In a further embodiment, the antioxidant is at least one of tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox168), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (referred to as Irganox1010), and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (referred to as Irganox1330).

[0023] The present invention also provides a method for preparing the flame retardant ABS composite material, comprising the following steps:

[0024] (1) Weigh 90-110 parts of ABS, 18-24 parts of flame retardant, 0.1-0.3 parts of compatibilizer SEBS-g-MAH, and 0.1-0.5 parts of antioxidant and mix them evenly to obtain a mixture;

[0025] (2) Extruding the mixture obtained in step (1) through a twin-screw extruder to form granules, thereby obtaining a flame-retardant ABS composite material.

[0026] The twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 180-210°C, zone two temperature 200-230°C, zone three temperature 200-230°C, zone four temperature 200-230°C, zone five temperature 200-230°C, zone six temperature 200-230°C; the head temperature of the twin-screw extruder is 200-230°C, and the screw speed is 200-270r / min.

[0027] The beneficial effects of the present invention are as follows:

[0028] (1) This patent first synthesizes antimony trisulfide, and then modifies it with 3-mercapto-2-methylpentanol to obtain 3-mercapto-2-methylpentanol-modified antimony trisulfide, and successfully introduces a mercapto group into antimony trisulfide; then, based on the principle that acyl chloride can react with mercapto groups to replace the sulfur atoms on the mercapto groups, thereby forming mercapto esters, it is further modified with 2-ethoxy-1-naphthoyl chloride to form a new flame retardant, namely, the flame retardant of this patent.

[0029] (2) The present invention synthesizes a flame retardant. Compared with commercially available antimony trisulfide, it introduces more benzene ring structures through modification. During the combustion process, the benzene ring structure can form a dense carbon layer, which can isolate the transfer of heat and oxygen, thereby preventing or slowing down the combustion process, and can well improve the flame retardant properties of ABS composite materials, which has great promotion value.

[0030] (3) The ABS composite material prepared by the present invention has excellent flame retardancy and material mechanical properties, and has great promotion significance. DETAILED DESCRIPTION

[0031] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood and comprehensive. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0032] The raw materials used in the following examples are as follows:

[0033] ABS (model 750A), Daqing Petrochemical; antimony nitrate, Hebei Shilan Chemical Technology Co., Ltd.; thiourea, Shandong Jinhe Chemical Co., Ltd.; ethanol, Jinan Mingxin Chemical Co., Ltd.; commercial antimony trisulfide, Shandong Haoyao New Materials Co., Ltd.; 3-mercapto-2-methylpentanol, Hubei Watson Chemical Technology Co., Ltd.; 2-ethoxy-1-naphthoyl chloride, Wuhan Guanxiang Chemical Co., Ltd.; N,N-dimethylformamide, Shandong Hengshuo Chemical Co., Ltd.; deionized water, Shanghai Lanyi Environmental Protection Technology Co., Ltd.; antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF, Germany; compatibilizer SEBS-g-MAH, Dongguan Xingyuan Chemical Co., Ltd.

[0034] The above reagents are only for illustrating the sources and components of the reagents used in the experiments of the present invention so as to fully disclose the information, and do not mean that the present invention cannot be realized by using other similar reagents or reagents provided by other suppliers.

[0035] Preparation Example 1

[0036] S1. Put 300 g of antimony nitrate, 360 g of thiourea, 600 g of ethanol and 1.0 kg of deionized water into a reaction vessel, and react in a 70° C. water bath for 10 h to obtain a first mixed solution.

[0037] S2. Filter the first mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 60° C. for 8 h to obtain antimony trisulfide.

[0038] S3. Put 300 g of antimony trisulfide, 80 g of 3-mercapto-2-methylpentanol, 500 g of ethanol, and 900 g of deionized water into a reaction vessel, and react in a 70° C. water bath for 12 h to obtain a second mixed solution.

[0039] S4. The second mixed solution is filtered, the obtained solid is washed and then placed in a vacuum drying oven at 70° C. and dried for 8 h to obtain antimony trisulfide modified with 3-mercapto-2-methylpentanol.

[0040] S5. Put 280 g of 3-mercapto-2-methylpentanol-modified antimony trisulfide, 100 g of 2-ethoxy-1-naphthoyl chloride, 400 g of N,N-dimethylformamide, 500 g of ethanol, and 700 g of deionized water into a reaction vessel, and react in a 70° C. water bath for 12 h to obtain a third mixed solution.

[0041] S6. Filter the third mixed solution, wash the obtained solid, and then dry it in a vacuum drying oven at 60° C. for 6 hours to obtain antimony trisulfide modified with 2-ethoxy-1-naphthoyl chloride, which is the flame retardant M1.

[0042] Example 1

[0043] (1) Weigh 90 parts of ABS, 18 parts of flame retardant M1, 0.1 parts of compatibilizer SEBS-g-MAH, and 0.1 parts of antioxidant Irganox1010, mix and stir evenly to obtain a mixture;

[0044] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P1.

[0045] The temperature and screw speed of each zone of the twin-screw extruder are: zone 1 temperature 180°C, zone 2 temperature 200°C, zone 3 temperature 200°C, zone 4 temperature 200°C, zone 5 temperature 200°C, zone 6 temperature 200°C, die head temperature 200°C, and screw speed 200r / min.

[0046] Preparation Example 2

[0047] S1. Put 400 g of antimony nitrate, 400 g of thiourea, 800 g of ethanol and 1.6 kg of deionized water into a reaction vessel, and react in a 90° C. water bath for 16 h to obtain a first mixed solution.

[0048] S2. Filter the first mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 90° C. for 14 hours to obtain antimony trisulfide.

[0049] S3. Put 400 g of antimony trisulfide, 100 g of 3-mercapto-2-methylpentanol, 600 g of ethanol, and 1.1 kg of deionized water into a reaction vessel, and react in a water bath at 80° C. for 16 h to obtain a second mixed solution.

[0050] S4. The second mixed solution is filtered, the obtained solid is washed and then placed in a vacuum drying oven at 90° C. and dried for 12 h to obtain antimony trisulfide modified with 3-mercapto-2-methylpentanol.

[0051] S5. Put 320 g of 3-mercapto-2-methylpentanol-modified antimony trisulfide, 140 g of 2-ethoxy-1-naphthoyl chloride, 480 g of N,N-dimethylformamide, 600 g of ethanol, and 900 g of deionized water into a reaction vessel, and react in a water bath at 80° C. for 16 hours to obtain a third mixed solution.

[0052] S6. Filter the third mixed solution, wash the obtained solid, and then dry it in a vacuum drying oven at 90° C. for 12 hours to obtain antimony trisulfide modified with 2-ethoxy-1-naphthoyl chloride, which is the flame retardant M2.

[0053] Example 2

[0054] (1) Weigh 110 parts of ABS, 24 parts of flame retardant M2, 0.3 parts of compatibilizer SEBS-g-MAH, 0.1 parts of Irganox 1010, 0.2 parts of Irganox 168, and 0.2 parts of Irganox 1330, mix and stir evenly to obtain a mixture;

[0055] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P2.

[0056] The temperature and screw speed of each zone of the twin-screw extruder are: zone 1 temperature 210℃, zone 2 temperature 230℃, zone 3 temperature 230℃, zone 4 temperature 230℃, zone 5 temperature 230℃, zone 6 temperature 230℃, die head temperature 230℃, screw speed 270r / min.

[0057] Preparation Example 3

[0058] S1. Put 350 g of antimony nitrate, 380 g of thiourea, 700 g of ethanol and 1.3 kg of deionized water into a reaction vessel, and react in a water bath at 80° C. for 13 h to obtain a first mixed solution.

[0059] S2. Filter the first mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 75° C. for 11 hours to obtain antimony trisulfide.

[0060] S3. Put 350 g of antimony trisulfide, 90 g of 3-mercapto-2-methylpentanol, 550 g of ethanol, and 1.0 kg of deionized water into a reaction vessel, and react in a 75° C. water bath for 14 h to obtain a second mixed solution.

[0061] S4. The second mixed solution is filtered, the obtained solid is washed and then placed in a vacuum drying oven at 80° C. and dried for 10 h to obtain antimony trisulfide modified with 3-mercapto-2-methylpentanol.

[0062] S5. Put 300 g of 3-mercapto-2-methylpentanol-modified antimony trisulfide, 120 g of 2-ethoxy-1-naphthoyl chloride, 440 g of N,N-dimethylformamide, 550 g of ethanol, and 800 g of deionized water into a reaction vessel, and react in a 75° C. water bath for 14 hours to obtain a third mixed solution.

[0063] S6. Filter the third mixed solution, wash the obtained solid, and then dry it in a vacuum drying oven at 75° C. for 9 hours to obtain antimony trisulfide modified with 2-ethoxy-1-naphthoyl chloride, which is the flame retardant M3.

[0064] Example 3

[0065] (1) Weigh 100 parts of ABS, 21 parts of flame retardant M3, 0.2 parts of compatibilizer SEBS-g-MAH, 0.1 parts of Irganox 168, and 0.2 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0066] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P3.

[0067] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 195°C, zone 2 temperature 215°C, zone 3 temperature 215°C, zone 4 temperature 215°C, zone 5 temperature 215°C, zone 6 temperature 215°C, die head temperature 215°C, and screw speed 235r / min.

[0068] Preparation Example 4

[0069] S1. 335 g of antimony nitrate, 389 g of thiourea, 635 g of ethanol, and 1.05 kg of deionized water were placed in a reaction vessel, and reacted in a 72° C. water bath for 13.5 h to obtain a first mixed solution.

[0070] S2. Filter the first mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 71° C. for 9.5 hours to obtain antimony trisulfide.

[0071] S3. 333 g of antimony trisulfide, 95 g of 3-mercapto-2-methylpentanol, 555 g of ethanol, and 1.08 kg of deionized water were placed in a reaction vessel, and reacted in a 79° C. water bath for 13 h to obtain a second mixed solution.

[0072] S4. The second mixed solution is filtered, the obtained solid is washed and then placed in a vacuum drying oven at 88° C. and dried for 9 hours to obtain antimony trisulfide modified with 3-mercapto-2-methylpentanol.

[0073] S5. Put 305 g of 3-mercapto-2-methylpentanol-modified antimony trisulfide, 115 g of 2-ethoxy-1-naphthoyl chloride, 445 g of N,N-dimethylformamide, 535 g of ethanol, and 805 g of deionized water into a reaction vessel, and react in a 73° C. water bath for 14.5 h to obtain a third mixed solution.

[0074] S6. The third mixed solution is filtered, the obtained solid is washed and then placed in a vacuum drying oven at 83° C. and dried for 7.6 h to obtain antimony trisulfide modified with 2-ethoxy-1-naphthoyl chloride, which is flame retardant M4.

[0075] Example 4

[0076] (1) Weigh 95 parts of ABS, 19 parts of flame retardant M4, 0.15 parts of compatibilizer SEBS-g-MAH, 0.1 parts of Irganox 1010, and 0.2 parts of Irganox 1330, mix and stir evenly to obtain a mixture;

[0077] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P4.

[0078] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 199°C, zone 2 temperature 225°C, zone 3 temperature 225°C, zone 4 temperature 225°C, zone 5 temperature 225°C, zone 6 temperature 225°C, die head temperature 225°C, and screw speed 255r / min.

[0079] Preparation Example 5

[0080] S1. 375 g of antimony nitrate, 398 g of thiourea, 735 g of ethanol, and 1.35 kg of deionized water were placed in a reaction vessel, and reacted in a water bath at 82° C. for 15 h to obtain a first mixed solution.

[0081] S2. Filter the first mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 88° C. for 13 hours to obtain antimony trisulfide.

[0082] S3. 345 g of antimony trisulfide, 98 g of 3-mercapto-2-methylpentanol, 575 g of ethanol, and 965 g of deionized water were placed in a reaction vessel, and reacted in a 74° C. water bath for 14 h to obtain a second mixed solution.

[0083] S4. The second mixed solution is filtered, and the obtained solid is washed and then placed in a vacuum drying oven at 76° C. and dried for 9 hours to obtain antimony trisulfide modified with 3-mercapto-2-methylpentanol.

[0084] S5. Put 305 g of 3-mercapto-2-methylpentanol-modified antimony trisulfide, 135 g of 2-ethoxy-1-naphthoyl chloride, 465 g of N,N-dimethylformamide, 525 g of ethanol, and 865 g of deionized water into a reaction vessel, and react in a 74° C. water bath for 15 hours to obtain a third mixed solution.

[0085] S6. The third mixed solution is filtered, the obtained solid is washed and then dried in a vacuum drying oven at 77° C. for 8 hours to obtain antimony trisulfide modified with 2-ethoxy-1-naphthoyl chloride, which is flame retardant M5.

[0086] Example 5

[0087] (1) Weigh 105 parts of ABS, 19 parts of flame retardant M5, 0.25 parts of compatibilizer SEBS-g-MAH, 0.1 parts of Irganox 1010, and 0.1 parts of Irganox 168, mix and stir evenly to obtain a mixture;

[0088] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P5.

[0089] The temperature and screw speed of each zone of the twin-screw extruder are: zone 1 temperature 200℃, zone 2 temperature 205℃, zone 3 temperature 205℃, zone 4 temperature 205℃, zone 5 temperature 205℃, zone 6 temperature 205℃, die head temperature 205℃, and screw speed 260r / min.

[0090] Comparative Example 1

[0091] (1) Weigh 105 parts of ABS, 0.25 parts of compatibilizer SEBS-g-MAH, 0.1 parts of Irganox 1010, and 0.1 parts of Irganox 168, mix and stir evenly to obtain a mixture;

[0092] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material D1.

[0093] The temperature and screw speed of each zone of the twin-screw extruder are: zone 1 temperature 200℃, zone 2 temperature 205℃, zone 3 temperature 205℃, zone 4 temperature 205℃, zone 5 temperature 205℃, zone 6 temperature 205℃, die head temperature 205℃, and screw speed 260r / min.

[0094] Comparative Example 2

[0095] (1) Weigh 105 parts of ABS, 19 parts of commercially available antimony trisulfide, 0.25 parts of compatibilizer SEBS-g-MAH, 0.1 parts of Irganox 1010, and 0.1 parts of Irganox 168, mix and stir to obtain a mixture;

[0096] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material D2.

[0097] The temperature and screw speed of each zone of the twin-screw extruder are: zone 1 temperature 200℃, zone 2 temperature 205℃, zone 3 temperature 205℃, zone 4 temperature 205℃, zone 5 temperature 205℃, zone 6 temperature 205℃, die head temperature 205℃, and screw speed 260r / min.

[0098] The ABS composite materials prepared in the above Examples 1-5 and Comparative Example 1 were made into strips for testing using an injection molding machine. The test data are shown in the following table:

[0099] Performance Test:

[0100] The flame retardant properties of the materials prepared in each embodiment and comparative example were tested according to the test standard UL94, the tensile strength was tested according to ASTM D638, the flexural modulus was tested according to ASTM D790, and the Izod notched impact strength was tested according to ASTM D256. The test results are shown in Table 1 below:

[0101] Table 1

[0102]

[0103] It can be seen from the above table:

[0104] In general, the flame retardant properties of P1-P5 are significantly better than those of D1-2, which indicates that the flame retardant properties of the ABS composite material of the present invention are better.

[0105] The physical properties of P1-P5 are comparable to those of D1-2, which indicates that adding the flame retardant of the present invention can improve the flame retardancy of the composite material without affecting the physical properties of the ABS composite material, which has a good practical application prospect.

[0106] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A flame retardant ABS composite material, characterized in that: Made from the following components in parts by weight: The flame retardant is antimony trisulfide modified by 2-ethoxy-1-naphthoyl chloride.

2. The flame retardant ABS composite material according to claim 1, characterized in that: The preparation method of the flame retardant is as follows: S1. Place antimony nitrate, thiourea, ethanol and deionized water into a reaction vessel, and react in a water bath at 70-90° C. for 10-16 hours to obtain a first mixed solution; S2, filtering the first mixed solution, washing the obtained solid, and drying it in a vacuum drying oven at 60-90° C. for 8-14 hours to obtain antimony trisulfide; S3, placing antimony trisulfide, 3-mercapto-2-methylpentanol, ethanol, and deionized water into a reaction vessel, and reacting in a 70-80° C. water bath for 12-16 hours to obtain a second mixed solution; S4, filtering the second mixed solution, washing the obtained solid, and drying it in a vacuum drying oven at 70-90° C. for 8-12 hours to obtain 3-mercapto-2-methylpentanol-modified antimony trisulfide; S5, adding antimony trisulfide modified with 3-mercapto-2-methylpentanol, 2-ethoxy-1-naphthoyl chloride, N,N-dimethylformamide, ethanol, and deionized water into a reaction vessel, and reacting in a water bath at 70-80° C. for 12-16 hours to obtain a third mixed solution; S6. Filter the third mixed solution by suction, wash the obtained solid, and then dry it in a vacuum drying oven at 60-90° C. for 6-12 hours to obtain antimony trisulfide modified with 2-ethoxy-1-naphthoyl chloride, which is a flame retardant.

3. The flame retardant ABS composite material according to claim 2, characterized in that: The mass ratio of antimony nitrate, thiourea, ethanol and deionized water in step S1 is (30-40): (36-40): (60-80): (100-160).

4. The flame retardant ABS composite material according to claim 2, characterized in that: The mass ratio of antimony trisulfide, 3-mercapto-2-methylpentanol, ethanol and deionized water in step S3 is (30-40): (8-10): (50-60): (90-110).

5. The flame retardant ABS composite material according to claim 2, characterized in that: The weight ratio of 3-mercapto-2-methylpentanol modified antimony trisulfide, 2-ethoxy-1-naphthoyl chloride, N,N-dimethylformamide, ethanol, and deionized water in step S5 is (28-32):(10-14):(40-48):(50-60):(70-90).

6. The flame retardant ABS composite material according to claim 1, characterized in that: The antioxidant is at least one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

7. The flame retardant ABS composite material according to claim 1, characterized in that: The compatibilizer is SEBS-g-MAH.

8. The method for preparing a flame retardant ABS composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh 90-110 parts of ABS, 18-24 parts of flame retardant, 0.1-0.3 parts of compatibilizer, and 0.1-0.5 parts of antioxidant and mix them evenly to obtain a mixture; (2) Extruding the mixture obtained in step (1) through a twin-screw extruder to form granules, thereby obtaining a flame-retardant ABS composite material.

9. The method for preparing the flame retardant ABS composite material according to claim 8, characterized in that: The twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 180-210°C, zone two temperature 200-230°C, zone three temperature 200-230°C, zone four temperature 200-230°C, zone five temperature 200-230°C, zone six temperature 200-230°C; the head temperature of the twin-screw extruder is 200-230°C, and the screw speed is 200-270r / min.